2015
DOI: 10.1097/aog.0000000000000608
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Cardiac Axis and Congenital Heart Defects in Early Gestation

Abstract: Abnormal cardiac axis is present in two-thirds of fetuses with congenital heart defect in early gestation. Adding cardiac axis assessment to the nuchal translucency measurement is helpful in defining a population at risk for fetal congenital heart defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 17 publications
2
39
1
1
Order By: Relevance
“…This is lower than the 26.4% reported by Syngelaki et al [2] and the 56% reported by Grande et al [3], but higher than in other previous studies [9,10]. In a protocol for first-trimester detection of anomalies, the use of a combination of markers such as NT, ductus venosus flow, tricuspid regurgitation, and measurement of the cardiac axis has the potential of significantly increasing detection rates [11][12][13].…”
Section: Discussioncontrasting
confidence: 54%
“…This is lower than the 26.4% reported by Syngelaki et al [2] and the 56% reported by Grande et al [3], but higher than in other previous studies [9,10]. In a protocol for first-trimester detection of anomalies, the use of a combination of markers such as NT, ductus venosus flow, tricuspid regurgitation, and measurement of the cardiac axis has the potential of significantly increasing detection rates [11][12][13].…”
Section: Discussioncontrasting
confidence: 54%
“…A recent review of the published series with more than 1,000 cases from 1993 to 2008, which included data from 36,237 pregnancies generated by eight centers, suggests that the overall detection rate of major CHD at 11-13 weeks is 29% (95% CI 25-33) [6] . The pooled detection rate of cardiac defects was 17% (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The authors suggested that the detection rate could be improved if the first-trimester ultrasound assessment followed very well-delineated protocols [31] .…”
Section: Clinical and Research Implicationsmentioning
confidence: 93%
“…Furthermore, normal tricuspid blood flow is a significant protective marker (LH-= 0.4). It has been widely demonstrated that first-trimester indirect signs, including NT, TR, ductus venosus (DV), and abnormal cardiac axis, are significantly associated with the risk of CHD [24,25] . The underlying mechanism of this association is uncertain.…”
Section: Interpretation Of the Findingsmentioning
confidence: 99%
“…Sinkovskaya et al [30] reported a normal variation in the cardiac axis from 34.5° at 11 weeks to 56.8° at 13 + 6 weeks of gestation, and that an abnormal cardiac axis can be associated with coarctation of the aorta, Ebstein's anomaly, transposition of the great vessels, and heterotaxy. The same group reported that 74.1% of fetuses with confirmed CHD had an abnormal cardiac axis when evaluated between 11 and 13 + 6 weeks/days of gestation [31] . In their study, the cardiac axis performed better than increased nuchal translucency, tricuspid regurgitation, or reversed atrial waveform in the ductus venosus in detecting major fetal cardiac defects.…”
Section: Ultrasound Findings Suggestive Of Fetal Cardiac Anomaliesmentioning
confidence: 95%